ANALISIS UNSUR INTRINSIK DAN NILAI MORAL DALAM CERPEN “WANITA BERWAJAH PENYOK” KARYA RATIH KUMALA - Erlin Puspitasari Prasetyo (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Ratih Kumala is a short story writer and novel who studies at Sebelas Maret University in the Faculty of English Literature, although his name is foreign, Ratih Kumala represented Indonesia at the 2019 Beijing International Book Fair (BIBF) which is the largest book exhibition in Asia. Researchers chose a short story titled "Woman with a dent face" by Ratih Kumala, which was very interesting to discuss, because the contents of the short story often happened to people. Various aspects of life that many children become victims of the sins of both parents, about a woman who is ostracized by the community and unwanted by both parents, lives alone in a small hut with a hand and foot in pasung, living the days with loneliness. This study aims to analyze the intrinsic elements and moral values in the short story "Woman with a Dent Face" by Ratih Kumala, while the interinsic elements are, theme, setting, plot, characterization, point of view, and mandate. The moral values contained in these short stories include, do not do things that are prohibited by religion, do not make fun of and discriminate between humans, patience, sincerity, and loyalty. The analysis of this research uses descriptive qualitative research methods. Steps to collect data in the short story "Woman with a Dent" by Ratih Kumala by (1) reading short stories intensively, then (2) analyzing intrinsic elements and their descriptions and (3) presenting data.